TINGKAT PENGETAHUAN MEMPENGARUHI KEPATUHAN DIET HIPERTENSI PADA LANSIA DI DESA WAIMITAL KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Hikmawati Hikmawati; Nur Baharia Marasabessy; Aulia Debby Pelu (Pusat Penelitian dan Pengabdian Kepada Masyarakat Poltekkes Kemenkes Maluku, 2022)
High blood pressure or hypertension is still a global and local health problem. One of the causes of hypertension is poor diet because they do not follow a hypertension diet properly. This can happen because of the patient's lack of knowledge about the diet itself. This study aims to determine the relationship between knowledge and dietary adherence to hypertension in the elderly in Waimital Village, Kairatu District, West Seram Regency. The research method used is descriptive analytic method with a cross sectional approach with a total sample of 40 respondents with hypertension. Sampling was done by total sampling technique. The data collection instrument used a questionnaire. The results showed that most of the respondents had a high level of knowledge (67.5%), and followed a hypertensive diet (62.5%). Statistical test results obtained p-value of 0.006 and p-value <0.05, which means that there is a relationship between the level of knowledge and adherence to a hypertension diet in the elderly. The level of respondent's knowledge was significantly related to hypertension diet compliance in the elderly with hypertension in Waitital Village, Kairatu District.